2010
DOI: 10.1039/b925439k
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations, sources and geochemistry of airborne particulate matter at a major European airport

Abstract: Monitoring of aerosol particle concentrations (PM 10 , PM 2.5 , PM 1 ) and chemical analysis (PM 10 ) was undertaken at a major European airport (El Prat, Barcelona) for a whole month during autumn 2007. Concentrations of airborne PM at the airport were close to those at road traffic hotspots in the nearby Barcelona city, with means measuring 48 mg PM 10 /m 3 , 21 mg PM 2.5 /m 3 and 17 mg PM 1 /m 3 . Meteorological controls on PM at El Prat are identified as cleansing daytime sea breezes with abundant coarse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…Considering that these elements can be related either to natural or anthropogenic sources, their enhancement in the main station can be explained by either the aircraft emissions or to soil resuspension by the activity at the airport. These observations are in line with those of Amato et al (2010) who observed elevated concentrations of Fe, Mg, Cu, Zn, Mn and Pb near the El Prat airport in Spain. It should be noted here that Zn and Cu that are typically related to emissions from combustion sources were not detected at the remote station, indicating that the influence of aviation to air quality is local at the vicinity of the airport.…”
Section: Elemental Compositionsupporting
confidence: 93%
See 1 more Smart Citation
“…Considering that these elements can be related either to natural or anthropogenic sources, their enhancement in the main station can be explained by either the aircraft emissions or to soil resuspension by the activity at the airport. These observations are in line with those of Amato et al (2010) who observed elevated concentrations of Fe, Mg, Cu, Zn, Mn and Pb near the El Prat airport in Spain. It should be noted here that Zn and Cu that are typically related to emissions from combustion sources were not detected at the remote station, indicating that the influence of aviation to air quality is local at the vicinity of the airport.…”
Section: Elemental Compositionsupporting
confidence: 93%
“…Its runway is 2.4-km long and is adjoined by a taxiway where aircrafts stay only for a short period of time (30 to 60 min). Depending on their schedule, some of the aircrafts are also being refuelled during their short stay at the airport; a process in the GRPs that is a major contributor to overall emissions related to the aviation activities (Amato et al, 2010;Hsu et al, 2013;Schlenker and Walker, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this light, it is plausible that corrosion and mechanical stress of some aircraft components may release metallic particles into the environment. For example, using scanning electron microscopy techniques, Amato et al (2010) founded the relatively common presence of platy aluminous particles derived from airframe corrosion in the ambient PM 10 samples collected near the El Prat airport in Barcelona.…”
Section: Other Mechanical Componentsmentioning
confidence: 99%
“…While air pollution remains a major concern for developing countries (Fenger, 2009;Liaquat et al, 2010) as a result of the rapid growth of population, energy demand and economic growth, developed countries have experienced a significant decline in the concentrations of many air pollutants over the past decade. Airport emissions (AEs) have received increasing attention in recent years because of the rapid growth of air transport volumes and the expected expansion to meet capacity needs for future years (Amato et al, 2010;Kurniawan and Khardi, 2011;Kinsey et al, 2011). Most studies highlight knowledge gaps (e.g., Webb et al, 2008;Wood et al, 2008a;Lee et al, 2010) which are a matter of concern as the literature indicates that aircraft emissions can significantly affect air quality near airports (Unal et al, 2005;Carslaw et al, 2006;Herndon et al, 2008;Carslaw et al, 2008;Mazaheri et al, 2009;Dodson et al, 2009) and in their surroundings (Farias and ApSimon, 2006;Peace et al, 2006;Hu et al, 2009;Amato et al, 2010;Jung et al, 2011;Hsu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The basic division of solid particles due to their aerodynamic diameter, allowed for the determination of two main groups: PM2.5 and PM10 (Particulate Matter) diameter respectively of less than 2.5 µm and 10 µm [4]. The dynamic development of research topics related to particulate matter properties change depending on their size forced an introduction of a more detailed division [5]. It was assumed that the smallest particles (ultrafine particles) have a diameter of less than 0.1 µm and fine particles (nanoparticles) less than 1 µm.…”
Section: Introductionmentioning
confidence: 99%